EFEKTIVITAS PENYUSUNAN RENCANA KERJA ANGGARAN (RKA) PADA KANTOR DINAS PENDAPATAN DAERAH PROVINSI SULAWESI TENGAH - Yudhiansyah, Yudhiansyah (Katalogis, 2015)
This Research Target is to analyse and know the compilation effectiveness Plan The Budget Job ( RKA) at Office On Duty Earnings of Middle Area Provinsi Sulawesi.Â This Research Type is research qualitative with the informan selected by the four of people. Data collecting use the technique interview and documentation. Technique analyse the data used by that is (1) Editing Data (2) Data Subdividing (3) Interpretation Mean the Data and (4) Withdrawal of Conclusion and Suggestion. Analyse the effectiveness by comparing budget and realization multiplied by]100 %. Result of Research Menunjukan (1) Compilation Plan The Budget Job ( RKA) in office On Duty Earnings of Middle Area Provinsi Sulawesi of]period 2010 - 2014 can be told by to have a criterion very effective. (2) Factors influencing Compilation Plan The Budget Job (RKA) in office On Duty Earnings of Middle Area Provinsi Sulawesi that is: (1) Resistor Factor, covering: (a) Not yet the existence of equality of mission and perception aparat from third institution that is Dispenda, Service of Raharja and Police. (b) The limited resource aparat of either through amount and also kualitas.(c) Not yet its[his] maximal is system of data and information in the field of management of finance of area earnings. (2) Impeller Factor, covering: (a) area Potency can be developed by as Original Earnings of Area (b) organizational Values like togetherness, innovate, and responsive and (c) Regulation - invitation of about area earnings